Pengaruh Gaya Komunikasi Dan Gaya Kepemimpinan Terhadap Loyalitas Barista Coffe Shop Medan - Maulida, Syakya; Nasution, Muhammad Lathief Ilhamy; Naser Daulay, Aqwa (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The study aim to know are there communication style and leadership style affect the loyalty of baristas in Medan coffee shops. The baristas in Medan City were the subjects of this study. The Associative Qualitative Method is the research technique employed; samples must fulfill the study specifications and have a minimum sample size of thirty respondents (Sugiyono, 2018: 138). Based on the data obtained from the distributed questionnaires, it results in a communication style that has a positive effect on barista loyalty. However, leadership style has no effect on barista loyalty